Cabozantinib in patients with platinum-refractory metastatic urothelial carcinoma: an open-label, single-centre, phase 2 trial. Issue 8 (August 2020) - Apolo, Andrea B; Nadal, Rosa; Tomita, Yusuke; Davarpanah, Nicole N; Cordes, Lisa M; Steinberg, Seth M; Cao, Liang; Parnes, Howard L; Costello, Rene; Merino, Maria J; Folio, Les R; Lindenberg, Liza; et al.
Summary: Background: Cabozantinib is a multikinase inhibitor of MET, VEGFR, AXL, and RET, which also has an effect on the tumour immune microenvironment by decreasing regulatory T cells and myeloid-derived suppressor cells. In this study, we examined the activity of cabozantinib in patients with metastatic platinum-refractory urothelial carcinoma. Methods: This study was an open-label, single-arm, three-cohort phase 2 trial done at the National Cancer Institute (Bethesda, MD, USA). Eligible patients were 18 years or older, had histologically confirmed urothelial carcinoma or rare genitourinary tract histologies, Karnofsky performance scale index of 60% or higher, and documented disease progression after at least one previous line of platinum-based chemotherapy (platinum-refractory). Cohort one included patients with metastatic urothelial carcinoma with measurable disease as defined by Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1. Two additional cohorts that enrolled in parallel (patients with bone-only urothelial carcinoma metastases and patients with rare histologies of the genitourinary tract) were exploratory. Patients received cabozantinib 60 mg orally once daily in 28-day cycles until disease progression or unacceptable toxicity. The primary endpoint was investigator-assessed objective response rate by RECIST in cohort one. Response was assessed in all patients who met the eligibility criteria and who received at least 8 weeks of therapy. All patients who received at least one dose of cabozantinib were included in the safety analysis. This completed study is registered with ClinicalTrials.gov, NCT01688999 . Findings: Between Sept 28, 2012, and Oct, 20, 2015, 68 patients were enrolled on the study (49 in cohort one, six in cohort two, and 13 in cohort three). All patients received at least one dose of cabozantinib. The median follow-up was 61·2 months (IQR 53·8–70·0) for the 57 patients evaluable for response. In the 42 evaluable patients in cohort one, there was one complete response and seven partial responses (objective response rate 19%, 95% CI 9–34). The most common grade 3–4 adverse events were fatigue (six [9%] patients), hypertension (five [7%]), proteinuria (four [6%]), and hypophosphataemia (four [6%]). There were no treatment-related deaths. Interpretation: Cabozantinib has single-agent clinical activity in patients with heavily pretreated, platinum-refractory metastatic urothelial carcinoma with measurable disease and bone metastases and is generally well tolerated. Cabozantinib has innate and adaptive immunomodulatory properties providing a rationale for combining cabozantinib with immunotherapeutic strategies. Funding: National Cancer Institute Intramural Program and the Cancer Therapy Evaluation Program.